P678 Ustekinumab therapy improves the nutritional status in patients with Crohn's Disease. A prospective study. (30th January 2023) - Bertani MD, L; D'Alessandro, C; Fornili, M; Coppini, F; Zanzi, F; Carmisciano, L; Geri, F; Baiano Svizzero, G; Ceccarelli, L; Mumolo, M G; Baglietto, L; Bellini, M; et al.
Abstract: Background: Patients with Crohn's disease (CD) display high rates of nutritional deficiencies and metabolic imbalances, primarily due to mucosal damage induced by inflammation. In particular, the loss of lean muscle mass configures a condition known as sarcopenia, which is not necessary associated with a low Body Mass Index (BMI). The presence of sarcopenia has been associated with a worst outcome of IBD. At present, no studies evaluated the impact of Ustekinumab (UST) in terms of its effects on body composition. The aim of this prospective study was to evaluate whether UST treatment could modify the parameters of body composition assessed by Bioelectrical Impedance Assay (BIA) in patients with CD. In particular, we evaluated phase angle, which represents the most clinically established impedance parameter and it might be considered as a reliable and optimal marker of nutritional status. Methods: We prospectively enrolled all consecutive CD patients treated with UST at our center, following the current guidelines. BIA was performed at baseline and at week 48, assessing Body Cellular Mass (BCM), total body water, phase angle and BMI. At the same time-points, a colonoscopy was performed in order to evaluate the therapeutic outcome in terms of mucosal healing, defined as a Simple Endoscopic Score for CD <2. We evaluated also clinical remission, defined as a Harvey-Bradshaw Index <5 at week 48. Results: Out of 44 patients enrolled, 26 (59%) presented clinical remission and 22 (50%) achieve mucosal healing at the end of follow up. No significant differences were observed at baseline in all the BIA parameters between responders and non-responders. Phase angle increased over time in responders, while this was not observed in non-responders (test for the interaction between time and outcome, p-value=0.010 and 0.008 for clinical remission and mucosal healing, respectively). The same differential increase was observed for BCM (test for the interaction between time and outcome, p-value=0.037 and 0.076 for clinical remission and mucosal healing, respectively). No other significant differences were observed regarding the other BIA parameters. Conclusion: UST therapy seems to be able to modify body composition of patients with CD. In particular, the increase in phase angle in responders suggests that a significant improvement of nutritional status occurred in these patients. Our results are in line to what was shown by a previous study performed in patients with psoriasis treated with UST.